2021
DOI: 10.1111/den.14118
|View full text |Cite
|
Sign up to set email alerts
|

Low risk of esophageal adenocarcinoma among patients with ultrashort‐segment Barrett's esophagus in Japan

Abstract: Objects Ultrashort‐segment Barrett’s esophagus (USSBE; length of <1 cm) is very frequently diagnosed in Japan, but the cancer risk of USSBE is unknown. In this study, by retrieving endoscopic images, we retrospectively investigated the incidence of esophageal adenocarcinoma (EAC) by the grade of Barrett’s esophagus (BE) and compared the findings with those of gastric cancer by the degree of endoscopic gastric atrophy in the same population. Methods Among consecutive participants who had undergone endoscopy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…It should be noted that this new concept of BO does not imply that all the BO in this category should undergo surveillance. On the contrary, we do not recommend endoscopic surveillance of ultrashort segment BO (USSBO) with less than 1 cm of columnar metaplasia since an overall risk of developing OAC is very low despite that it has an increased risk per unit area comparable to short segment BO (SSBO) with 1–3 cm of columnar metaplasia (SSBO) 37…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that this new concept of BO does not imply that all the BO in this category should undergo surveillance. On the contrary, we do not recommend endoscopic surveillance of ultrashort segment BO (USSBO) with less than 1 cm of columnar metaplasia since an overall risk of developing OAC is very low despite that it has an increased risk per unit area comparable to short segment BO (SSBO) with 1–3 cm of columnar metaplasia (SSBO) 37…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent retrospective cohort study in Japan reported that although the prevalence of USSBE is high (36.4%), the incidence of adenocarcinoma in USSBE is very low (0.0068% per year). 49 In addition, the aforementioned annual incidence of 0.47% of adenocarcinoma from SSBE longer than 2 cm, in Japan, 41 may be an important indicator for future stratification of Barrett's esophagus.…”
Section: Barrett's Esophagus As a Target For Surveillancementioning
confidence: 99%
“…At the initial diagnosis, the Seattle biopsy protocol, which entails four‐quadrant biopsies every 2 cm in addition to targeted biopsies of macroscopically visible lesions, is recommended if the columnar lining is greater than 1 cm above the EGJ in most Western guidelines. 49 , 65 However, the protocol is time‐consuming, practicing endoscopists have poor adherence to it, and there is an increased risk associated with the large number of biopsy samples required. 66 Since the majority of BE is SSBE, targeted biopsies are the standard protocol for endoscopic observation in Japan.…”
Section: Diagnosis Of Bementioning
confidence: 99%
“…Because of cases of over-and under-diagnosis, we demonstrated that the variance was unacceptably large (17.2%-96.8%),and the diagnostic accuracy was inadequate, especially in cases with a BE length of less than 1 cm, suggesting that the minimum length of CLE should be defined in future criteria in Japan. 48 Although most studies show that the incidence of EAC in BE of less than 1 cm in length is very low, 49 Barrie et al recently reported that almost 20% of all dysplasia in BE and EAC occurs within a centimeter of the EGJ, suggesting that all lengths of CLE above the EGJ should be recognized as BE and subjected to a thorough biopsy protocol. 50 Traditionally, BE is divided into long-segment BE (LSBE, ≥3 cm) and SSBE (<3 cm) based on the length of columnar mucosa in the distal esophagus as assessed by endoscopy.…”
Section: What Is the Optimal Landmark For The Egj?mentioning
confidence: 99%